Molecular and cytogenetic analysis of the telomeric (TTAGGG)n repetitive sequences in the Nile tilapia, Oreochromis niloticus (Teleostei: Cichlidae) - Chew, Joyce S. K.; Oliveira, Claudio [UNESP]; Wright, Jonathan M.; Dobson, Melanie J. (Springer Nature, 2002)
The majority of chromosomes in Oreochromis niloticus, as with most fish karyotyped to date, cannot be individually identified owing to their small size. As a first step in establishing a physical map for this important aquaculture species of tilapia we have analyzed the location of the vertebrate telomeric repeat sequence, (TTAGGG)n, in O. niloticus. Southern blot hybridization analysis and a Bal31 sensitivity assay confirm that the vertebrate telomeric repeat is indeed present at O. niloticus chromosomal ends with repeat tracts extending for 4-10 kb on chromosomal ends in erythrocytes. Fluorescent in situ hybridization revealed that (TTAGGG)n is found not only at telomeres, but also at two interstitial loci on chromosome 1. These data support the hypothesis that chromosome 1, which is significantly larger than all the other chromosomes in the karyotype, was produced by the fusion of three chromosomes and explain the overall reduction of chromosomal number from the ancestral teleost karyotype of 2n=48 to 2n=44 observed in tilapia.
Keywords: animal cell; animal experiment; aquaculture; chromosome 1; chromosome analysis; controlled study; erythrocyte; female; fluorescence in situ hybridization; gene sequence; karyotype; male; nonhuman; oreochromis niloticus; Southern blotting; teleost; telomere; Tilapia; vertebrate; animal; genetics; karyotyping; metabolism; nucleotide repeat; pulsed field gel electrophoresis; Animalia; Cichlidae; Oreochromis niloticus; Teleostei; Vertebrata; deoxyribonuclease; DNA; exonuclease Bal 31; Animals; Blotting, Southern; Electrophoresis, Gel, Pulsed-Field; Endodeoxyribonucleases; Female; In Situ Hybridization, Fluorescence; Karyotyping; Male; Repetitive Sequences, Nucleic Acid; Telomere